Recent Advances in Functional Nanomaterials for Diagnostic and Sensing Using Self-Assembled Monolayers - Basso, Caroline R. [UNESP]; Crulhas, Bruno P. [UNESP]; Castro, Gustavo R. [UNESP]; Pedrosa, Valber A. [UNESP] (MDPI, 2023)
Functional nanomaterials have attracted attention by producing different structures in any field. These materials have several potential applications, including medicine, electronics, and energy, which provide many unique properties. These nanostructures can be synthesized using various methods, including self-assembly, which can be used for the same applications. This unique nanomaterial is increasingly being used for biological detection due to its unique optical, electrical, and mechanical properties, which provide sensitive and specific sensors for detecting biomolecules such as DNA, RNA, and proteins. This review highlights recent advances in the field and discusses the fabrication and characterization of the corresponding materials, which can be further applied in optical, magnetic, electronic, and sensor fields.
Keywords: nanostructures; self-assemblies; sensor